The Data Shake Opportunities and Obstacles for Urban Policy Making - Concilio, Grazia; Pucci, Paola; Raes, Lieven; Mareels, Geert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This open access book represents one of the key milestones of PoliVisu, an H2020 research and innovation project funded by the European Commission under the call (3z(BPolicy-development in the age of big data: data-driven policy-making, policy-modelling and policy-implementation(3y(B. It investigates the operative and organizational implications related to the use of the growing amount of available data on policy making processes, highlighting the experimental dimension of policy making that, thanks to data, proves to be more and more exploitable towards more effective and sustainable decisions. The first section of the book introduces the key questions highlighted by the PoliVisu project, which still represent operational and strategic challenges in the exploitation of data potentials in urban policy making. The second section explores how data and data visualisations can assume different roles in the different stages of a policy cycle and profoundly transform policymaking.s
Part 1: The data shake: open questions and challenges for policy making -- Cha[ter 1. The data shake: an opportunity for experiment-driven policy making -- Chapter 2. data ownership and open data: the potential for data-driven policy making -- Chapter 3. Towards a public sector data culture: data as an individual and communal resource in progressing democracy -- Chapter 4. Innovation in data visualisation for public policy making -- Part 2: The PoliVisu project -- Chapter 5. Policy-related decision making in a smart city context: the polivisu approach -- Chapter 6. Turning data into actionable policy insights -- Chapter 7. Data-related ecosystems in policy making. the polivisu contexts -- Chapter 8. Making policies with data: the legacy of the polivisu project.
Keywords: Geography; Sociology, Urban; Urban policy; Regional Geography; Urban Sociology; Urban Policy